Determination Leadership Spiritual, Culture Organization, Competence, Service on Religious Performance Through Spiritual Motivation - Harianto, Harianto; Wibisono, Chablullah; Lestari, RA Widyanti Diah (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
Introduction/ Objectives: Study This aim for know spiritual leadership , culture organization , competition , service to religious performance through spiritual motivation . Methods: Method Which used in study This is method mixed Methods. This research combines two existing forms of research: qualitative and quantitative. The research method uses a causal model survey using path analysis techniques. Results: The results show that spiritual leadership determinate significant to spiritual motivation on private hospital of lhokseumawe city, aceh province .organizational culture, competence, service. the next results show that spiritual leadership, organization culture, service, spiritual motivation determinate significant to religious performance on private hospital of lhokseumawe city, aceh province. and the last results show that spiritual leadership, organtization culture, competence, and service determinate significant to religious performance through spiritual motivation on private hospital of lhokseumawe city, aceh province. Conclusion: Based on conclusion which obtained from this study, there is some suggestions that can made into reference for increase performance religious Private Hospital Nurses in Lhokseumawe City, Aceh Province. Suggestions for Spiritual Leadership and Spiritual Motivation, namely with push training program development spiritual leadership for leader at home pain to strengthen spiritual motivation of employees. Spiritual Leadership and Religious Performance are: provide a platform or forum for leaders and employees for share practice best related spiritual performance in environment Work.